2019
DOI: 10.1111/1440-1630.12625
|View full text |Cite
|
Sign up to set email alerts
|

Evidence based practice and knowledge translation: A survey of Australian occupational therapy practice with clients experiencing neurocognitive impairments

Abstract: Introduction:The clinical practice patterns and use of research evidence by Australian occupational therapists working with clients experiencing neurocognitive impairments has not been surveyed for nearly 10 years. This survey aimed to evaluate the current status of occupational therapy practice and evidence use and provide recommendations for ongoing evidence translation. Methods: An online survey of occupational therapists working in Australia was conducted over four months targeting registered clinicians wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 23 publications
2
10
0
2
Order By: Relevance
“…Use of functional training, task modification and compensatory training identified by participants to treat EFI are deemed traditional practice approaches used in cognitive rehabilitation, and consistent with clinical practice in previous surveys (Koh et al, 2009;Korner et al, 2011;Nott et al, 2020). In comparison, this study also identified use of goal setting which is less cited in literature exploring occupational therapy practice in cognitive rehabilitation, with the exception of recent multidisciplinary studies (Downing et al, 2019;Nowell et al, 2020).…”
Section: Interventionssupporting
confidence: 72%
See 1 more Smart Citation
“…Use of functional training, task modification and compensatory training identified by participants to treat EFI are deemed traditional practice approaches used in cognitive rehabilitation, and consistent with clinical practice in previous surveys (Koh et al, 2009;Korner et al, 2011;Nott et al, 2020). In comparison, this study also identified use of goal setting which is less cited in literature exploring occupational therapy practice in cognitive rehabilitation, with the exception of recent multidisciplinary studies (Downing et al, 2019;Nowell et al, 2020).…”
Section: Interventionssupporting
confidence: 72%
“…The questionnaire was developed from a literature review of occupational therapy practice for the management of EFI completed by the principal author. The author also contacted an author of a clinical survey undertaken in Australia in 2020 (Nott et al, 2020) Operational definitions for key terms were identified and provided to participants.…”
Section: Survey Designmentioning
confidence: 99%
“…Nevertheless, understanding the process of EBP in occupational therapy also includes, in parallel, identifying barriers to its use. Intriguingly, despite the available literature suggesting that EBP is widely perceived as positive by occupational therapists, several studies identified the lack of confidence and skills in appraising research analysis as a common obstacle to applying research-based knowledge in occupational therapy practice [4,6,8,[16][17][18]. Moreover, some studies also indicated that limited time available, restrictions on access to research literature, fieldwork educators not practicing EBP, and/or putting higher value on clinical experience rather than research were seen as barriers particularly relevant to clinical settings or the workplace [4,6,7,[16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…La formation devrait également agir sur les croyances des proches aidants à ce sujet. L’enseignement sur les méthodes optimisant l’apprentissage et leur application à des situations rencontrées viendrait ainsi pallier le fait que les interventions utilisées auprès des personnes vivant avec un TNCM sont majoritairement compensatoires (Nott et al, 2020). Ces interventions telles que la livraison de repas ou l’aide au bain, bien qu’aidantes pour le maintien à domicile, permettent rarement l’utilisation des capacités préservées chez la personne vivant avec un TNCM.…”
Section: Discussionunclassified
“…Les travaux d’Amieva et ses collaborateurs (2012) soutiennent que les proches aidants souhaitent recevoir de l’information sur la maladie, son évolution, les traitements possibles ainsi que sur les habiletés nécessaires pour optimiser le soutien de la personne vivant avec un TNCM. Or, la plupart des services actuellement offerts à ces personnes et à leurs proches sont de nature compensatoire (Nott, Barden, Chapparo, & Ranka, 2020). Permettant peu l’utilisation des capacités préservées des personnes vivant avec un TNCM, les interventions compensatoires entraînent souvent des refus de services et l’apparition d’expressions comportementales des troubles neurocognitifs (symptômes comportementaux et psychologiques de la démence [SCPD]), dont certains sont connus comme des facteurs pouvant précipiter l’admission en ressource d’hébergement en institution (Okura et al, 2011).…”
Section: Problématiqueunclassified